The Relationship Between The Level of Knowledge and The Way of Handling Burns In Employees of The Fire Department of Palembang City - Qonitah Muhsinah; Tri Suciati; Iqmal Perlianta (Sriwijaya Journal of Medicine, 2024)
Burns are injuries characterized by damage to skin tissue due to direct contact with a source that conducts heat. Some action activities that have a high risk of burns are firefighters. This reflects that the level of knowledge and handling of burns is very important and becomes the main focus as a firefighter. This study aims to determine the relationship between the level of knowledge and how to handle burns on fire department employees in Palembang. This study was an observational analytic study with a case series approach. with a sample of Fire Department Employees in Palembang. The data used is primary data derived from questionnaires. Researchers recorded data such as age, gender, education, level of knowledge of burns, and knowledge of how to treat burns. 180 people met the research criteria. The dominating characteristics were age 26-35 years (58.3%), male (81.7%), female (18.3%), the level of knowledge about burns was in the good category (40.5%). And knowledge of how to handle burns is in the good category (61.7%). Analysis using bivariate analysis found that there was a significant correlation between the level of knowledge and how to handle burns (p=0.000; r=0.452). Most respondents in this study were aged 26-35 years, male and had a Diploma / Bachelor's degree. The level of knowledge about burns and how to handle them was mostly in the good category. In the correlation test, there was a significant correlation between the level of knowledge and how to handle burns.